Frequency discrimination in rats exposed to noise as juveniles - Šuta, Daniel; Rybalko, Natalia; Shen, Da-Wei; Popelář, Jiří; Poon, Paul W F; Syka, Josef (Physiology & behavior, 2015)
Sound exposure during the early postnatal period can significantly influence the function of the auditory system in rats during adulthood. In the present study, rat pups (strain Long-Evans) were exposed to broad-band noise at 125dB SPL for 8, 12 or 25min on postnatal day 14 and then at the age of 3-5months their frequency discrimination at 4 and 16kHz was assessed using a modified method of the prepulse inhibition of the acoustic startle reflex. In all groups of exposed rats, an altered frequency discrimination of the tonal stimuli was observed, in comparison with controls, at 70dB SPL. A worsening of frequency discrimination was observed even in animals exposed for 8min, the auditory thresholds of which were almost identical to that of control animals. The individual auditory thresholds did not correlate with frequency discrimination. The difference in frequency discrimination between the exposed and control animals disappeared at 85-90dB SPL. Our data suggests that brief noise exposure during the critical period of development results in the altered frequency discrimination at moderate sound intensities in adult rats, which may appear even in individuals with normal hearing thresholds.
Keywords: akustická stimulace; úleková reakce; Analysis of Variance; Animals; Auditory Threshold; novorozená zvířata; sluchové kmenové evokované potenciály; Female; Acoustic Stimulation; ženské pohlaví; Rats, Long-Evans; hluk; Time Factors; časové faktory; Animals, Newborn; sluchový práh; analýza rozptylu; potkani Long-Evans; Male; Prepulse Inhibition; prepulsní inhibice; krysa rodu Rattus; psychoakustika; Reflex, Startle; zvířata; mužské pohlaví; Psychoacoustics; elektroencefalografie; Evoked Potentials, Auditory, Brain Stem; Noise; Rats; Electroencephalography